Social networking as an advertising tool in Russia and abroad; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Ageev I. A. Iliya Aleksandrovich; Kondratyeva (Kondratieva) I. V. Irina Vladimirovna; Zaviyalova Z. S. Zinaida Sergeevna; Giniyatova E. V. Elena Vladimirovna; Zavyalova M. P.; Deakin A. K. Ann; Lokotosh Y. V. (2016, 2016)
Title screen